Queering language revitalisation navigating identity and inclusion among queer speakers of minority languages - Walsh, John 1971- (Cambridge elements, 2025)
This Element aims to deepen our understanding of how the fields of multilingualism, second language acquisition and minority language revitalisation have largely overlooked the question of queer sexual identities among speakers of the languages under study. Based on case studies of four languages experiencing differing degrees of minoritisation - Irish, Breton, Catalan and Welsh - it investigates how queer people navigate belonging within the binary of speakers/non-speakers of minoritised languages while also maintaining their queer identities. Furthermore, it analyses how minoritised languages are dealing linguistically with the growing need for 'gender-fair' or 'gender-neutral' language. The marginalisation of queer subjects in these strands of linguistics can be traced to the historical dominance of the Fishmanian model of 'Reversing Language Shift' (RLS), which assumed the importance of the deeply heteronormative model of 'intergenerational transmission' of language as fundamental to language revitalisation contexts